Disaster Mitigation Communication Pattern of West Java Province of Social Services in the Time of the Pandemic Covid-19 - Saefudin, Iing; Iqbal, Mochamad; Asri F, Charisma (Budapest International Research and Critics University, 2021)
According to the Ministry of Social Affairs, the provinces in Indonesia are very prone to disasters. This is due to the geographical location, topographical conditions, climatic conditions, but the terrain, demographic factors, and socio-economic conditions of the people who are prone to disasters. There needs to be a communication process as a social radar that can provide news to other parties as disaster risk reduction. This study aims to be able to analyze the communication patterns of disaster mitigation carried out by the West Java Provincial Social Service in preparing for disaster preparedness and to find out the barriers to disaster mitigation communication, especially during the Covid-19 pandemic. The research was conducted using qualitative descriptive methods such as observations and interviews. The results showed that the West Java Social Service had a disaster mitigation communication pattern based on the Main Tasks of Disaster Management and it was formulated in the form of the TAGANA (Disaster Alert) program for Disaster Alert Village (KSB), TAGANA Entering School, and Planting Mangrove Trees. The implementation of disaster mitigation programs during the Covid-19 pandemic follows health protocols such as distributing masks, checking body temperature, washing hands, and maintaining distance. Semantic barriers become obstacles that hinder disaster mitigation.